2005
DOI: 10.1111/j.1462-2920.2005.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary succession of soil Crenarchaeota across a receding glacier foreland

Abstract: The development of soil archaeal community structures in relation to primary succession in bulk and rhizosphere soil was examined across the forefield of the receding Rotmoosferner glacier in Austria. Using cloning and denaturing gradient gel electrophoresis (DGGE) analysis of reverse transcription polymerase chain reaction (RT-PCR) products of extracted 16S rRNA, archaeal community structure was compared over a chronosequence representing approximately 150 years of soil development and to reference sites outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(181 citation statements)
references
References 42 publications
9
168
3
1
Order By: Relevance
“…The AOA amoA gene copy numbers decreased along an altitudinal gradient of Mount Everest, whereas that of AOB did not shift significantly with altitude (Zhang et al 2009). More recently, a study in the rhizosphere of a boreal forest tree indicated a decrease of archaeal diversity under soil warming (Bomberg et al 2011) which is consistent with previous findings in a receding glacier foreland of Austria (Nicol et al 2005. In addition, soil moisture has been reported as a major factor affecting soil N mineralization, which influences the N availability, along a temperature gradient in four European shrubland ecosystems (Beier et al 2008).…”
Section: Responses Of Aob and Aoa Abundance To Soil Warming And Fertisupporting
confidence: 76%
“…The AOA amoA gene copy numbers decreased along an altitudinal gradient of Mount Everest, whereas that of AOB did not shift significantly with altitude (Zhang et al 2009). More recently, a study in the rhizosphere of a boreal forest tree indicated a decrease of archaeal diversity under soil warming (Bomberg et al 2011) which is consistent with previous findings in a receding glacier foreland of Austria (Nicol et al 2005. In addition, soil moisture has been reported as a major factor affecting soil N mineralization, which influences the N availability, along a temperature gradient in four European shrubland ecosystems (Beier et al 2008).…”
Section: Responses Of Aob and Aoa Abundance To Soil Warming And Fertisupporting
confidence: 76%
“…For DGGE analysis of dsrB amplicons, a denaturant gradient of 40-80% was used. Electrophoresis was carried out on a DCode Universal Mutation Detection System (Bio-Rad, Hemel Hempstead, UK) in 7 L of 1 Â TAE buffer at a constant temperature of 60 1C for 960 min at 75 V. Silver staining of gels was carried out as previously described (Nicol et al, 2005). All DGGE gels included three lanes with a standard set of 11 marker bands (see Supplementary Methods).…”
Section: Denaturing Gradient Gel Electrophoresismentioning
confidence: 99%
“…Cloning and phylogenetic analysis DNA was extracted from the cell resuspension (950 ml) as described by Griffiths et al (2000) as modified by Nicol et al (2005). Approximately 1357 bp fragments of bacterial 16S rDNA were obtained by a nested PCR using the primers pA/pH 0 and pB/pG 0 for the first and second amplifications, respectively (Edwards et al, 1989).…”
Section: Microtox Analysismentioning
confidence: 99%
“…Plasmids were extracted using the Qiagen plasmid extraction kit (Qiagen). Clone libraries were screened by PCR amplification using primers for positions 341-534 in Escherichia coli (Muyzer et al 1993) and Denaturing Gradient Gel Electrophoresis performed as described previously (McKew et al, 2007), except gels were silver-stained as described by Nicol et al (2005). Representative clones from each library were selected and sequenced using the primer pG 0 (Edwards et al, 1989) (Source Bioscience Ltd., Cambridge, UK).…”
Section: Microtox Analysismentioning
confidence: 99%